KEEFEKTIFAN KONSELING KELOMPOK COGNITIVE BEHAVIOR UNTUK MENINGKATKAN REGULASI DIRI SISWA SMP - Bakhrudin All Habsy (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2019)
Self regulation is a process of self-regulation to set a mind and feeling to achieve a goal to be achieved. Self regulation determines student success, because students who have self-regulation can plan, evaluate, and control themselves. This study aims to determine the effectiveness of cognitive behavior group counseling can improve self-regulation of junior high school students. This study, using an experimental design with the Nonequivalent Control Group Design design. The data normality test results show that the control group is not normally distributed where the Sig.Asymp is smaller than 0.05. Whereas for the experimental group is normally distributed, where Sig.Asymp is greater than 0.05. Then it is obtained a hypothesis test that is appropriate for the control group using Wilcoxon test and for the experimental group using paired samples t test. Wilcoxon test results showed Sig.Asymp (2-tailed) of 0.080> 0.05, meaning that without giving counseling the Cognitive behavior group in the control group was not effective in improving student self-regulation, while for the paired samples t test test results showed Sig.Asymp ( 2-tailed) of 0.003 <0.05 means that the counseling behavior of Cognitive behavior groups in the experimental group is effective in enhancing student self-regulation. The research was carried out starting from April 2018 to January 2019, which took place at SMP Islam Mbah Bolong Jombang. Based on the results of the research, researcher gives suggestions for: 1) Teachers of Counseling Guidance, can be used as a reference that Cognitive behavior group counseling services can improve student self-regulation, 2) For further research: can apply Cognitive behavior counseling and can use different techniques in group counseling services so that they will gain a broader insight